Review on the Impacts of the Samalas Eruption (1257 CE) to the Hydrogeological Conditions of Mataram, Lombok, Indonesia - Malawani, Mukhamad Ngainul; Hadmoko, Danang Sri; Lavigne, Franck; Agniy, Romza Fauzan; Hayat, Dimas Maula; Astabella, Relinda Dewi; Laksono, Agung; Syamsuddin, Syamsuddin; Mutaqin, Bachtiar Wahyu (Geological Agency, 2024)
This paper examines the local impacts of the 1257 CE Samalas eruption in the Mataram plain in relation to the hydrogeological conditions. Data from several previous studies in the Mataram plain is summarized and then reinterpreted. Data collected from new fieldwork is also presented. This review summarizes hydrogeological conditions into several categories, i.e. stratigraphy, aquifer formation, groundwater quality, and evolution. Two coring data were evaluated, which showed that Mataram plain has a relatively thick alluvial layer with a dominant material of sand mixed with pumice from the reworked deposit of the 1257 CE Samalas eruption. The sediment from this eruption formed a freshwater aquifer layer up to 18 m deep. Using resistivity data, the aquifer layers in the studied area were characterized as unconfined aquifer, aquitard, and semi-unconfined aquifer. Seven water samples show that the groundwater in the studied area is in good condition, which indicates the bicarbonate water type. The results of the analysis show that the impact of the 1257 CE Samalas eruption on the hydrogeology of Mataram is considered a positive impact, i.e. forming an unconfined aquifer containing freshwater that is good for domestic uses.